Dependence of fire proof efficiency of nonwoven polyester material from the chemical nature of nitrogen and phosphorus-containing flame retardant - Reva, Olga V.; Bogdanova, Valentina V.; Lukyanov, Alexander S.; Perevoznikov, Sergey S.; Andreeva, Tatiana N. (Journal of the Belarusian State University. Chemistry, 2017)
The comparative researches the efficiency of nitrogen and phosphorus-containing burning retardants, containing nitrogen in ammonium (synthetic dispersions of ammonium phosphates of two- and trivalent metals) or in amino-imino form (5 amino-tetrazole phosphate) were conducted for finding the factors with determining impact on stability the fireproof handling the polyester materials for washings. Before the fireproof handling it was carried out the preliminary activation the polyester matrix in the mixture of 10 % solutions of acetic and sulfuric acids with the subsequent endurance in a spirit tin chloride solution. By comparative researches of fire protected with studied burning retardants polyester material it was established that the fireproof effect, stable against washings, manages to be reached only in case of application the colloid-containing dispersion of the ammonium phosphates of two- and trivalent metals. At the same time it was found that without the polyester surface preliminary activation the fireproof effect, stable against washings, can’t be reached. It was assumed that fixing the nitrogen and phosphorus-containing burning retardants, stable against water handlings, on the polyester material can be reached by interaction the chemical adsorbed on a polymeric substrate colloidal particles of bivalent tin compounds with colloidal particles of metal-containing dispersion; whereas the nitrogen-containing component chemical nature doesn’t exert the determining impact on to burning retardants fixing on a polyester matrix.
Keywords: flame retardants; fire protection; polyester; dispersion; colloidal particles